Antimicrobial and Insecticide Resistance in Vector-Borne Disease Systems: A Dual-Threat Review - Harbi, Abdullah Ali Yahya; Mashragi, Ibrahim Mohammed Ahmed; Alharbi, Khalid Ahmed Mohammed; Khormi, Ibrahim Yahya Ahmed; Aamri, Hadi Mohammed Hadi; Huthan, Anwar Hamuod Zed; Al Refaei, Yahya Talal Ahmed; Qaysi, Samia Abdullah; Al-Harbi, Maher Hamdan; Alamoudi, Eiman Omar; Almajnuni, Fawaz Mohammed; Hakami, Radiah Saree; et al. (Journal of Ecohumanism, 2024)
Background: Vector-borne diseases remain a significant global health burden, and their control depends heavily on antimicrobials to manage pathogens and insecticides to suppress vectors. However, resistance to both interventions has accelerated in recent years. The simultaneous rise of antimicrobial resistance (AMR) in pathogens and insecticide resistance (IR) in vectors poses a critical dual challenge that threatens the effectiveness of disease prevention, treatment, and outbreak response. Objective: To systematically review the current evidence on antimicrobial and insecticide resistance within major vector-borne disease systems, describe resistance mechanisms and drivers, and assess their combined impact on disease control efforts. Methods: A systematic search of PubMed, Scopus, Web of Science, and Google Scholar was conducted for studies published between 2000 and 2024. Eligible studies reported AMR patterns in pathogens or IR patterns in disease-transmitting vectors (e.g., Anopheles, Aedes, Culex, Phlebotomus, Triatoma). Data were extracted on resistance prevalence, molecular mechanisms, contributing environmental and operational factors, and implications for public health interventions. Findings were synthesized narratively due to study heterogeneity. Results: The review identified widespread insecticide resistance, particularly to pyrethroids, organophosphates, and carbamates, driven by metabolic enzyme overexpression, target-site mutations (e.g., kdr mutations), and behavioral adaptations. Similarly, pathogens such as Plasmodium, Leishmania, and arboviruses exhibited increasing antimicrobial resistance linked to genetic mutations, drug pressure, and treatment misuse. Environmental changes, agricultural pesticide application, rapid urbanization, and inconsistent public health practices were major factors accelerating both AMR and IR. The co-occurrence of these resistance forms significantly reduces the effectiveness of vector control interventions, increases disease transmission, and complicates outbreak response strategies. Conclusion: Antimicrobial and insecticide resistance represent interconnected and escalating threats within vector-borne disease systems. Addressing this dual challenge requires integrated, multisectoral approaches that include genomic surveillance, rational insecticide and drug use, vector control innovation, and strengthened stewardship policies. Coordinated global action is essential to preserve current tools and sustain disease control gains.